Odpowiedzi

2010-03-19T18:25:43+01:00
A) 9x² - 1 = 0
9x²=1
x²=1/9
x=⅓ lub x=-⅓

b) 2x² = 8x
2x²-8x=0
x(2x-8)=0
x=0 lub 2x-8=0
2x=8
x=4

c) -x² + 8x -16 ≥ 0
-x²+8x-16=0
Δ=b²-4ac
Δ=8²-4*(-1)*(-16)=64-64=0
x=-b/2a
x=-8/(2*(-1))
x=-8/-2=4
x =4

d) x² + 5 > 3x
x²-3x-5=0
Δ=b²-4ac
Δ=(-3)²-4*1*(-5)=9+20=29
x1=(-b-√Δ)/2a
x1=(3-√29)2
x2=(-b+√Δ)/2a
x2=(3+√29)2
x∈(-∞;(3-√29)2) suma((3+√29)2; +∞)

e) 3x² = 12x
3x²-12x=0
3x(x-4)=0
3x=0 ∨ x-4=0
x=0 x=4

f) 4x² - 1 = 0
4x²=1
x²=¼
x=½ ∨ x=-½

g) -x² + 4x - 7 < 0
-x²+4x-7=0
Δ=b²-4ac
Δ=4²-4*(-1)*(-7)=16-28=-12
x∈ do zbioru pustego

h) x² + 25 ≤ 10x
x²-10x+25=0
Δ=b²-4ac
Δ=(-10)²-4*1*25=100-100=0
x=-b/2a
x=10/2=5
x=5
2010-03-19T18:37:02+01:00